The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12351-018-0403-4
|View full text |Cite
|
Sign up to set email alerts
|

Two metaheuristic approaches for solving the multi-compartment vehicle routing problem

Abstract: We address in this paper a multi-compartment vehicle routing problem (MCVRP) that aims to plan the delivery of different products to a set of geographically dispatched customers. The MCVRP is encountered in many industries, our research has been motivated by petrol station replenishment problem. The main objective of the delivery process is to minimize the total driving distance by the used trucks. The problem configuration is described through a prefixed set of trucks with several compartments and a set of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Klodawski et al [15] generated a simulation model of VRP with dynamic information in the FlexSim. Yahyaoui et al [16] proposed a GA based on partially matched crossover to solve the multi-compartment vehicle routing problem in oil delivery and found that solutions generated by the proposed algorithm on all involved standard cases were optimal. On the basis of the above research results, several types of VRP optimization models have been built.…”
Section: State Of the Artmentioning
confidence: 99%
“…Klodawski et al [15] generated a simulation model of VRP with dynamic information in the FlexSim. Yahyaoui et al [16] proposed a GA based on partially matched crossover to solve the multi-compartment vehicle routing problem in oil delivery and found that solutions generated by the proposed algorithm on all involved standard cases were optimal. On the basis of the above research results, several types of VRP optimization models have been built.…”
Section: State Of the Artmentioning
confidence: 99%
“…Differential Evolution (DE) algorithm with a triangular mutation operator is proposed to solve the optimization problem [22] and applied to the stochastic programming problems [23]. Many researchers presented the applications of metaheuristic algorithms in different types of problems such as unconstrained function optimization [24], vehicle routing problems [25][26][27], machine scheduling [28,29], mine production schedules [30], project selection [31], soil science [32], feature selection problem [33,34], risk identification in supply chain [35] etc. For constrained optimization problems, Particle Swarm Optimization (PSO) with Genetic Algorithm (GA) was presented and compared to other metaheuristic algorithms [36].…”
Section: Figure 1: Classification Of Metaheuristic Algorithmsmentioning
confidence: 99%
“…The algorithm stops when it gets an individual that solves the problem, has the main fitness utility or when the population converges, it means not find a better individual for many generations [3]. Promising results for GA are found in several problems, such as the metaheuristic approach to the multi-compartment vehicle routing problem (MCVRP) using voracious and genetic algorithm [4] and in the optimization of routes of trained vehicles [5].…”
Section: Motivationmentioning
confidence: 99%